The significance of resilience in mental health promotion of marriage immigrant women: a qualitative study of factors and processes - Yeonjae Jo (BMC, 2020)
Abstract Background This study explores a series of processes in which marriage immigrant women achieve positive mental health status after experiencing various marriage- and migrant-related difficulties through the framework of resilience theory. As marriage immigrant women face greater barriers to public health services than non-immigrant women, it is necessary to understand the related factors, process, and context to address these barriers and strengthen available assets. Methods A qualitative case study design was used with the phenomenological approach. Eleven mental health promotion program managers and 12 marriage immigrant women from who experienced resilience were recruited from four public-funded multicultural community centers in Seoul and Gyeonggi-do, South Korea, between December 2015 and March 2016. Using data from in-depth semi-structured face-to-face interviews, the author applied theme analysis informed by the resilience theory in order to identify factors that affect resilience and its development process. Results Findings indicated that the process of resilience follows enduring difficulties, collapse of stability, access to professional help, professional and social support, and experience of growth. A combination of the staged process of growth, absence of partner support, children as a driving force for change, the need for economic activity, factors affecting difference in growth: satisfaction levels of women's need for recognition, respect, and reward, and level of spousal support were identified as factors affecting marriage immigrant women's resilience. Conclusions Spouses, children, and economic activity play key roles in resilience in positive and negative ways. The existing information barrier should be addressed at a structural level to improve the mental health of marriage immigrant women, and the optimum time for intervention is suggested within 2 years post-migration. Efforts to build supportive relationships with Korean spouses and meet the women's needs for recognition, respect, and reward may also help promote these women's resilience.